Investigating the implementation of a new protocol and clinical tool designed to assess the audiological needs of individuals with hearing loss in clinical settings - Mathieu Hotton; Mathieu Hotton; Loonan Chauvette; Sandie Poulin; Jean-Pierre Gagné; Jean-Pierre Gagné (Frontiers in Audiology and Otology)
IntroductionFew clinical protocols are presently available to guide hearing healthcare professionals who are responsible for conducting comprehensive audiological needs assessments with their clients. The Québec Audiological Assessment Protocol for Younger and Older Adults (QAAP-YOA) was recently developed for this purpose. This pilot study is the third phase in the development of the QAAP-YOA. Its objective was to assess the implementation of the QAAP-YOA in clinical settings.MethodsAudiologists (n = 5) and adults with hearing loss (n = 29) participated in the study. Audiologists were trained to use the QAAP-YOA. Then, they administered the QAAP-YOA to clients. Needs assessment reports and QAAP-YOA clinical tools written by audiologists following these assessments were analyzed. Data related to the audiologists' workflow were collected. Individual semi-structured interviews were also conducted with participants to explore their experience.ResultsAudiologists judged the QAAP-YOA relevant and useful. It allowed them to perform more comprehensive and consistent needs assessments, and to formulate more adequate recommendations. Compliance ratings for assessment reports were higher after training (p < 0.001), particularly when the clinical tool was used. Participants were satisfied with the QAAP-YOA, but longer appointments and additional time for record keeping was required to implement it.ConclusionsAudiologists can benefit from using the QAAP-YOA. Digitalizing the clinical tool may help reduce the time required to administer the procedure, facilitate its use and allow for possibility of adapting the protocol to specific clientele and work settings.